Macrocirculatory and Microcirculatory Endpoints in Sepsis Resuscitation. (December 2021) - Mok, Garrick; Hendin, Ariel; Reardon, Peter; Hickey, Michael; Gray, Sara; Yadav, Krishan
Sepsis is a common disease process encountered by physicians. Sepsis can lead to septic shock, which carries a hospital mortality rate in excess of 40%. Although the Surviving Sepsis Guidelines recommend targeting a mean arterial pressure (MAP) of 65 mmHg and normalization of lactate, these endpoints do not necessarily result in tissue perfusion in states of shock. While MAP and lactate are commonly used markers in resuscitation, clinicians may be able to improve their resuscitation by broadening their assessment of the microcirculation, which more adequately reflects tissue perfusion. As such, in order to achieve a successful resuscitation, clinicians must optimize both macrocirculatory (MAP, cardiac output) and microcirculatory (proportion of perfused vessels, lactate, mottling, capillary refill time) endpoints. This review will summarize various macrocirculatory and microcirculatory markers of perfusion that can be used to guide the initial resuscitation of patients with sepsis.